The balancing of rotating machinery as nonlinear system - Menh, Nguyen Cao (Vietnam Journal of Mechanics, 1999)
In this paper a method for dynamical balancing of rotating machines as a nonlinear system is proposed. After analyzing and identifying the nonlinear system, procedure of dynamical balance including measurement and processing of vibration signals, for calculating magnitude and location of imbalance mass is presented. An example of simulation and calculation is investigated for illustration of the method.